Review of Social Collaborative Filtering Recommender System’s Methods (International Journal of Engineering and Computer Science, 2015)
Recommender Systems plays a vital role in e-commerce. The goal of recommender system is to present the user with the personalized information that matches with the user’s interest. Now a days, user’s interest is leaning towards social networks. Social Networking Sites provide users a platform to connect and share their information with other users who share similar interests with user. The popularity of social networking sites is increasing day by day. Recommender systems are now using the social information for their analysis and prediction process. Collaborative filtering approach is assumed to be the broadly approved technique of recommender system. Collaborative filtering method recommends an item to a user based on the preferences of other users who share analogous interest with the active user. In this paper, we have presented a study of collaborative filtering based social recommender system.